A Regional Analysis of Diversity, Equity, and Inclusion Initiatives in Plastic Surgery Residency Programs - Dylan G. Choi, BS; Kevin Luu, BS; Gabrielle Brite, BA; Alexander T. Plonkowski, MBBS, MRes; Mariam Al-Hamad Daubs, MD; Aleksandra Krajewski, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Residents seek inclusive training environments that prioritize diversity. To evaluate programs that focus on these elements, websites have become essential for applicants but often lack in diversity, equity, and inclusion (DEI) content. Thus, this study aimed to assess current efforts and attention to DEI within plastic surgery residency programs and compare them by region. Methods:. A retrospective review of Accreditation Council for Graduate Medical Education plastic surgery residency program websites was conducted. Various elements of DEI were identified on each program's page and were compared based on geographic region. Results:. Upon review, 82 residency programs were identified. Of these programs, 40 (48.7%) mentioned at least 1 element of DEI on their website, 38 (46.3%) promoted gender affirmation surgery as a part of their program, 29 (35.4%) mentioned advocacy, and 39 (47.6%) showcased at least 1 publication/presentation about DEI. Between the regions, there was no statistically significant difference in mention of DEI or perceptible representation in leadership. However, there was a significant difference in the mention of gender affirmation surgery, with the Northeast having the most mention (74.1%, P = 0.006). In addition, there was a significant difference in DEI research featured on websites, with the West having the highest rate of features (69.2%, P = 0.019). Conclusions:. This study demonstrates the variance of different aspects of DEI on plastic surgery websites. To foster diverse prospective applicants, plastic surgery residency programs must be aware of these paucities and address them accordingly.